The Impact of South China Sea Dispute on National Interests and Sovereignty of Indonesia - Abraham, Patrick; Raijaya, Iga Karishma Maharani (Green Publisher, 2025)
This study aims to examine the impact of the dynamics of the South China Sea dispute on the national interests and sovereignty of the Unitary State of the Republic of Indonesia. This study uses a qualitative research method with data analysis techniques consisting of data reduction, data presentation, and drawing conclusions. The theories used in this study are the theories of sovereignty, national interests, and geopolitics. The results of this study indicate that the dynamics of the dispute in the South China Sea region have shown signs of escalation that encourage the formation of expansionist geopolitics in regional countries. This condition can ultimately disrupt the achievement of the national interests of the Unitary State of the Republic of Indonesia and can threaten the sovereignty of the Unitary State of the Republic of Indonesia, especially in the Natuna waters. The Government of the Unitary State of the Republic of Indonesia is considered necessary to strengthen the maritime military, in this case the Indonesian Navy or TNI AL, to ward off traditional and non-traditional security threats, and optimize diplomacy through a regional approach to encourage the formation of a Code of Conduct (Coc) in the South China Sea region as soon as possible.